The lipid-linked oligosaccharide donor specificities of Trypanosoma brucei oligosaccharyltransferases - Izquierdo, Luis (Oxford University Press, 2012)
We recently presented a model for site-specific protein N-glycosylation in Trypanosoma brucei whereby the TbSTT3A oligosaccharyltransferase (OST) first selectively transfers biantennary Man(5)GlcNAc(2) from the lipid-linked oligosaccharide (LLO) donor Man(5)GlcNAc(2)-PP-Dol to N-glycosylation sequons in acidic to neutral peptide sequences and TbSTT3B selectively transfers triantennary Man(9)GlcNAc(2) to any remaining sequons. In this paper, we investigate the specificities of the two OSTs for their preferred LLO donors by glycotyping the variant surface glycoprotein (VSG) synthesized by bloodstream-form T. brucei TbALG12 null mutants. The TbALG12 gene encodes the α1-6-mannosyltransferase that converts Man(7)GlcNAc(2)-PP-Dol to Man(8)GlcNAc(2)-PP-Dol. The VSG synthesized by the TbALG12 null mutant in the presence and the absence of α-mannosidase inhibitors was characterized by electrospray mass spectrometry both intact and as pronase glycopetides. The results show that TbSTT3A is able to transfer Man(7)GlcNAc(2) as well as Man(5)GlcNAc(2) to its preferred acidic glycosylation site at Asn263 and that, in the absence of Man(9)GlcNAc(2)-PP-Dol, TbSTT3B transfers both Man(7)GlcNAc(2) and Man(5)GlcNAc(2) to the remaining site at Asn428, albeit with low efficiency. These data suggest that the preferences of TbSTT3A and TbSTT3B for their LLO donors are based on the c-branch of the Man(9)GlcNAc(2) oligosaccharide, such that the presence of the c-branch prevents recognition and/or transfer by TbSTT3A, whereas the presence of the c-branch enhances recognition and/or transfer by TbSTT3B.